A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera - Nassirkhani, Mahrad; Zaragoza, Juan A.; Mumladze, Levan (Zootaxa, 2019)
A new genus and species of epigean pseudoscorpions belonging to the subfamily Neobisiinae Chamberlin, 1930, is described from western Georgia and its diagnostic characters are illustrated. Cornuroncus n. gen. resembles the genus Roncus L. Koch, 1873 in several characters but differs by having a short dorso-distal spine on tarsus IV, and the presence of a ventral tooth on one of the claws of tarsus IV. An identification key for all valid Neobisiinae genera is provided.